Revitalizing educational methods in the quran and hadith to foster 21st-century skills (4c) - Siska Margareta; Charles; Iswantir; Rahmi Siregar (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2024)
The educational methods based on the Qur'an and Hadith, particularly the educational approach of the Prophet Muhammad, hold great potential in shaping students' character and skills. However, in the modern era, these methods are often forgotten. This research aims to revitalize the Islamic educational methods found in the Qur'an and Hadith and to analyze their potential in developing 21st-century skills among Muslim students. Through a literature study that analyzes various sources, including tafsir books, Hadith, Islamic education books, journals, and related articles, this research examines six main methods: qudwah (exemplification), lectures, question and answer, demonstrations, mujadalah (discussions), and amtsal (metaphors). The research results indicate that these six methods have great potential in fostering 21st-century skills such as critical thinking, creativity, collaboration, and effective communication. For instance, through the qudwah method, teachers can become inspiring role models for students in applying these skills. Meanwhile, the lecture method helps students understand basic theories and inspiring examples, while also stimulating them to think more critically, creatively, and to boldly ask questions or express opinions. The mujadalah method encourages students to engage in discussions and exchange ideas actively, thereby enhancing their collaboration and communication skills. The amtsal method helps students understand complex concepts by simplifying them through analogies, which promotes creativity, collaboration, and more effective communication skills. Revitalizing the Islamic educational methods based on the Qur'an and Hadith is an important step toward improving the quality of Islamic education.